Hukuman Mati bagi Koruptor sebagai Solusi Pemberantasan Korupsi di Indonesia: Analisis Konstitusional dan Dampak Hukumnya - Agus Damai Lase (Verdict: Journal of Law Science, 2026)
Corruption is an extraordinary crime that has wide-ranging impacts on various aspects of national and state life in Indonesia. Efforts to eradicate corruption have not yet produced satisfactory results, even though legal instruments such as Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, the establishment of the Corruption Eradication Commission, and various national policies are already in place. One discourse that has re-emerged is the imposition of the death penalty for perpetrators of corruption as a more repressive form of law enforcement. This study examines two main issues: (1) how the death penalty for corruptors is regulated in Indonesia, and (2) what impacts arise from the implementation of the death penalty for corruption offenders. This research employs a normative juridical method with a statute approach and an analytical approach, through the examination of the constitution, legislation, legal literature, and expert opinions. The results of the study indicate that the application of the death penalty in corruption crimes is normatively possible under certain conditions, as regulated in Article 2 paragraph (2) of the Anti-Corruption Law. However, its implementation remains debated from the perspectives of constitutionality, human rights, deterrence effectiveness, and its socio-political impacts. The application of the death penalty for corruptors has the potential to create a deterrent effect on corruption crimes, but it does not automatically serve as a single solution. A comprehensive approach is required through improvements in the political system, public administration, and law enforcement to achieve effective corruption eradication. Thus, it can be concluded that although the death penalty may be considered an extraordinary measure under certain conditions, its implementation must adhere to the principles of constitutionality, human rights, proportionality, and legal accountability.